2021
DOI: 10.3390/atmos13010034
|View full text |Cite
|
Sign up to set email alerts
|

Potential Contribution of Climate Conditions on COVID-19 Pandemic Transmission over West and North African Countries

Abstract: COVID-19, caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), is a very contagious disease that has killed many people worldwide. According to data from the World Health Organization (WHO), the spread of the disease appears to be slower in Africa. Although several studies have been published on the relationship between meteorological parameters and COVID-19 transmission, the effects of climate conditions on COVID-19 remain largely unexplored and without consensus. However, the transmiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 57 publications
7
11
0
Order By: Relevance
“…Correlations with humidity and water vapor characteristics exhibited significant and positive values over the Sahelian and Gulf of Guinea countries and negative values over the Maghreb countries. The results also demonstrated that COVID-19 pandemic transmission is affected differently by the three climatic regions: (i) cold and dry environmental conditions; (ii) warm and humid environmental conditions; and (iii) cold and humid environmental conditions [32].…”
Section: Temperature Humidity and Wind Speedmentioning
confidence: 79%
See 3 more Smart Citations
“…Correlations with humidity and water vapor characteristics exhibited significant and positive values over the Sahelian and Gulf of Guinea countries and negative values over the Maghreb countries. The results also demonstrated that COVID-19 pandemic transmission is affected differently by the three climatic regions: (i) cold and dry environmental conditions; (ii) warm and humid environmental conditions; and (iii) cold and humid environmental conditions [32].…”
Section: Temperature Humidity and Wind Speedmentioning
confidence: 79%
“…This result explains why the frequency of cases in various African and Asian nations has decreased in recent months. However, even though this was the result, more research is still needed to figure out why the COVID-19 pandemic reacts differently to the weather conditions in different parts of Africa [32].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Kendall rank correlation test has demonstrated to be less sensitive to errors and discrepancies in data compared to Pearson or Spearman tests (e.g., Diouf et al, 2022). Finally, the orographydependent temperature/precipitation biases are also examined.…”
Section: B Evaluation Metricsmentioning
confidence: 99%